Co-creation in circular cities: A design perspective - Huang, Li-Ting; Villari, Beatrice (My University, 2021)
The release of the European Green Deal for the circular economy has made more and more municipal authorities embed circular economy principles into their visions and strategies, fostering the transitions towards a “circular city”. Collaborative practices are becoming familiar, and concepts such as co-creation are entering the policymaking vocabulary, indicating that citizens and other actors are being asked to work collaboratively towards a sustainable future. This also means re-designing systems and services in cities with the aim of tackling emerging social and environmental issues and co-creating innovation paths. However, co-creation as an approach for implementing a circular economy at the city level has not yet been thoroughly investigated. The aim of this paper is to outline a framework that can be used by cities to identify new opportunities for co-creation initiatives from a design perspective. Using a three-step research process: (i) literature review, (ii) case study analysis and (iii) results interpretation, this paper delineates nine co-creation categories for sustainable development and identifies stakeholders and tools to be adopted by seeing circular economy principles as the ultimate goal.
Keywords: Circular City; Co-creation framework; Circular Economy